The reasons for Chinese nursing staff to report adverse events: a questionnaire survey. (27th February 2017) - Hong, Su; Li, QiuJie
Abstract : Aims: To investigate the impact of nurses' perception of patient safety culture and adverse event reporting, and demographic factors on adverse event reporting in Chinese hospitals. Background: Accurate and timely adverse event reporting is integral in promoting patient safety and professional learning around the incident. Methods: In a cross‐sectional survey, a sample of 919 nurses completed a structured questionnaire composed of two validated instruments measuring nurses' perception of patient safety culture and adverse event reporting. Associations between the variables were examined using multiple linear regression analysis. Results: The positive response rates of five dimensions of the Patient Safety Culture Assessment Scale varied from 47.55% to 80.62%. The accuracy rate of Adverse Event Reporting Perception Scale was 63.16%. Five hundred and thirty‐one (58.03%) nurses did not report adverse event in past 12 months. Six variables were found to be associated with nurses' adverse event reporting: total work experience ( P = 0.003), overall patient safety culture score ( P < 0.001), safety climate ( P < 0.001), teamwork climate ( P < 0.001), overall the adverse event reporting perception scale score ( P = 0.003) and importance or reporting ( P = 0.002). Conclusions: The results confirmed that improvements in the patient safety culture and nurses' perception of adverse event reporting were related to an increase in voluntary adverse event reporting. Implications for Nursing Management: The knowledge of adverse event reporting should be integrated into the patient safety curriculum. Interventions that target a specific domain are necessary to improve the safety culture.